2018
DOI: 10.15243/jdmlm.2018.053.1207
|View full text |Cite
|
Sign up to set email alerts
|

Review of the occurrence and structural controls of Baryte resources of Nigeria

Abstract: Baryte occurrences in Nigeria are spread across the Cretaceous Benue Trough which comprises of carbonaceous shales, limestone, siltstones, sandstones as well as in the northeastern, northwestern and southeastern parts of the Precambrian Basement Complex comprising of metasediments and granitoids. The mineralization is structurally controlled by NW-SE, N-S and NE-SW fractures. The common mode of occurrence for these barytes is the vein and cavity deposits type usually associated with galena, sphalerite, copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…High concentrations of heavy metals ingested from plants can damage central and peripheral nervous systems, bloods, lungs and liver (Adaramodu et al, 2012;Ogwuegbu and Mahanga, 2005). Labe et al, (2018) reported the occurrence of barites as vein mineralization and the associated gangue minerals include galena, sphalerite, copper sulphide, quartz and iron oxide which might be sources of Pb, Zn, Cu, Si and Fe in the soils where these fluted pumpkins are grown.…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of heavy metals ingested from plants can damage central and peripheral nervous systems, bloods, lungs and liver (Adaramodu et al, 2012;Ogwuegbu and Mahanga, 2005). Labe et al, (2018) reported the occurrence of barites as vein mineralization and the associated gangue minerals include galena, sphalerite, copper sulphide, quartz and iron oxide which might be sources of Pb, Zn, Cu, Si and Fe in the soils where these fluted pumpkins are grown.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are indications that the barytes also formed along fault planes through the Precambrian Basement Complex underlying the Cretaceous sediments, as evidenced in Bunde -Lessel mine (near Orgba) where the vein walls are brecciated (Figures 4a,b) and the host rocks include some basement gneisses. There are several mineral gangue associations with baryte; among others, Lead-zincbaryte mineralisation has been recorded in the BT (Ene et al, 2012;Labe et al, 2018) (Figure 2). Quartz, fluorite, talc, iron ores, antimony, etc were also noted in the study area.…”
Section: Study Area and Geological Settingmentioning
confidence: 97%
“…Figure 2. Distribution of lead-zinc-baryte mineralisation along the Benue Trough (modified fromEne et al, 2012 -after Cratchley andJones, 1965;and Labe et al, 2018).…”
mentioning
confidence: 99%
“…However, further studies on some barite deposits have shown that mining of barite deposits below 15 m depth produces medium-to high-quality grades of barite (Afolayan 2017;Inyang et al 2013;MMSD 2016;Oden 2012). In addition, some notable research and exploration studies report on the low, medium, and high grades with the recommendation that further processing is done to evaluate the potential of few identified high-grade deposits (Chaanda et al 2010;Labe et al 2018;Mgbemere et al 2018a, b;Oden 2012). Barite ore requires some upgrading to minimum purity, specific gravity, and composition with qualities needed in drilling and other industrial activities (Ibrahim et al 2017;MMSD 2010;NGSA 2010).…”
Section: Introductionmentioning
confidence: 99%